2021
DOI: 10.1016/j.ultsonch.2021.105862
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriostatic effects of high-intensity ultrasonic treatment on Bacillus subtilis vegetative cells

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…They are also acknowledged as the main source of ROS, mainly originating from the respiratory chain [ 14 ]. Various environmental stressors, such as pesticides, are known to enhance ROS production and disturb cellular redox homeostasis [ 15 , 16 , 17 , 18 ]. Our data confirmed that CHL treatment caused rapid ROS accumulation in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…They are also acknowledged as the main source of ROS, mainly originating from the respiratory chain [ 14 ]. Various environmental stressors, such as pesticides, are known to enhance ROS production and disturb cellular redox homeostasis [ 15 , 16 , 17 , 18 ]. Our data confirmed that CHL treatment caused rapid ROS accumulation in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…For scanning electron microscopy (SEM), samples were diluted to 0.05 mg/mL with deionized water of the corresponding pH value. Diluted samples (10 μL) were added to clean slides, air-dried for 24 h, and then observed with a scanning electron microscope (Apreo 2C; Thermo Fisher Scientific, Waltham, MA, USA) at an acceleration voltage of 10 kV ( Luo et al, 2021 ; Wang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Untreated and HIU-treated (US-270, US-90, US-360) bacterial cells were centrifuged at 6790× g for 10 min at 4°C, rinsed in PBS (pH 7.2) buffer three times, and then stored at −80°C (cryopreservation) ( Li, et al, 2020 ; Luo et al, 2021 ). The collected Salmonella cells were lysed by the lysis solution (pH 8.1, 100 mM Tris-HCl, 1.5% SDS) and the total protein was precipitated through acetone.…”
Section: Methodsmentioning
confidence: 99%